MID-UPPER DNIEPER PATOIS LEXICON: THE REGISTERED LEXEMES MAPPING - Мартинова, Ганна (Linguistic Bulletin (Movoznavchyi Visnyk), 2020)
The article represents basics for the concept of compiling a Mid Upper Dnieper patois lexicon, as well as featuring and interpreting its lexemes, with the emphasis on the principal lexicography foundations – the representation of the lexemes according to the patois grouping. Purpose. Representing various mapping variants for the registered lexicon verified within the Mid Upper Dnieper patois area. Results. Registered stock is classified according to the lingua geographical area principle, the lexemes being divided into non contrastive and contrastive, the latter distinguished into types and subtypes on the basis of common semantic meaning for the lexemes, of the actually common root morpheme (with different word building peculiarities), of the actual common lexeme for the semantic differences, of the different phonetic features and the peculiar grammar. In the lexical register the area differentiation is fully reflected in the lexical, semantic, word building, phonetic, accent bound and grammatical variants of the registered lexemes. Originality. The article originally represents the applied area principle in the lexicography practice. The lexemes registered under the Mid Upper Dnieper area according to the patois texts are represented in connection with their location within patois groups. Conclusion. The peculiarity of the stock of the Mid Upper Dnieper patois lies in representing registered lexemes according to groups (central, northern, eastern, western, southern ones) or indicating their spread within the area that enables thorough study for the stock under consideration. According to the area principle, the registered stock represents non-contrastive lexical dialectal differences demonstrating traditional basic and spiritual culture of the speakers, as well as contrastive ones being realized in lexical, semantic, word building, phonetic, accentual and grammatical variations of the registered words. The approach has been analyzed in the entries in which lexemes or their variations have been registered according to the patois groups, so that to arrange the information on the spread of the registered lexemes in the Mid Upper Dnieper area, to demonstrate their inner division according to the lexical stock and to this effect it is quite promising to be applied in other lexicography works.